(untitled) (Italian Review of Legal History, 2024)
Article 1 of Royal Decree No. 2325 of 1928 (Provisions for legislative unification in the territories annexed to the Kingdom) established that from July 1, 1929, the Italian codes of civil law, commercial law and civil procedure were to come into force in the territories of the former Austrian monarchy annexed by the Kingdom of Italy. However, Article 4 specified that «Until further notice, the rules governing the Trieste Commodities Exchange remained in force and the arbitration proceedings shall also be maintained», because the Italian government realized how much more convenient it was to preserve, rather than repeal, the special provisions on commercial arbitration at the Trieste Commodities Exchange. Consequently, with the approval of the ministerial decree of June 21, 1929, the new Procedural rules on arbitration at the Trieste Mercantile Exchange came into force. These new rules transposed into Italian law the old Austrian provisions contained in the 1912 Statute of the Trieste Commodities Exchange concerning the «arbitration judgements», so as to coordinate their wording with that of other Italian laws. The Hapsburg model thus adapted to the Italian reality proved to be particularly resilient, since it was not abandoned even with the entry into force of the new Code of Civil Procedure of 1942, let alone after the end of fascism and the birth of the Italian Republic.